2011
DOI: 10.1111/j.1440-1843.2010.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor (TREM‐1) expressed on myeloid cells predicts bacteremia better than clinical variables in community‐acquired pneumonia

Abstract: This preliminary study suggests that the determination of sTREM-1 serum levels on admission may be more accurate than clinical variables for identifying bacteremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…The authors concluded that plasma sTREM-1 had moderate diagnostic performance in differentiating sepsis from SIRS. Moreover, some researchers have suggested that PCT and CRP are more sensitive biomarkers than sTREM-1 for diagnosis of bacterial infection [32, 33]. In the present study, we found that plasma sTREM-1 and PCT values, as well as APACHE II score, were significantly higher in patients with sepsis than in patients with SIRS.…”
Section: Discussionsupporting
confidence: 60%
“…The authors concluded that plasma sTREM-1 had moderate diagnostic performance in differentiating sepsis from SIRS. Moreover, some researchers have suggested that PCT and CRP are more sensitive biomarkers than sTREM-1 for diagnosis of bacterial infection [32, 33]. In the present study, we found that plasma sTREM-1 and PCT values, as well as APACHE II score, were significantly higher in patients with sepsis than in patients with SIRS.…”
Section: Discussionsupporting
confidence: 60%
“…However, Blijlevens et al [50] questioned the value of PCT levels in sepsis diagnosis. Ruiz-Gonzalez et al [51] recently suggested that sTREM-1 levels are valuable for diagnosing bacteremia with community-acquired pneumonia. Because fewer studies have shown the value of sTREM-1 in the diagnosis of bacteremia, we divided ICU patients with fever into blood culture-positive bacteremia and blood culture-negative groups based on their blood culture results.…”
Section: Discussionmentioning
confidence: 99%
“…Such biomarkers include CRP, procalcitonin and triggering receptor expressed on myeloid cells (TREM-1). TREM-1 is a member of the immunoglobulin superfamily, is up-regulated by microbial products [124] and may stimulate secretion of several cytokines and chemokines [125]. The serum soluble TREM-1 was associated with bacteremic CAP [125] while soluble TREM-1 in bronchoalveolar lavage fluid was associated with bacterial pneumonia [124].…”
Section: Current Methods Of Diagnosing Pneumococcal Pneumoniamentioning
confidence: 99%